Centrality dependence of subthreshold ϕ meson production in Ni + Ni collisions at 1.9A GeV - Piasecki, Krzysztof; Herrmann, Norbert; Deppner, Ingo Martin; Liu, Jian-Li; Merschmeyer, Markus; Pelte, Dietrich; Reischl, Andreas; Wisniewski, Krzysztof; Zinyuk, Victoria (Physical review, 2016)
We analyzed the ϕ meson production in central Ni + Ni collisions at a beam kinetic energy of 1.93A GeV with the FOPI spectrometer and found a production probability per event of [8.6±1.6(stat)±1.5(syst)]×10−4. This new data point allows us for the first time to inspect the centrality dependence of subthreshold ϕ meson production in heavy-ion collisions. The rise of ϕ meson multiplicity per event with mean number of participants can be parametrized by a power function with exponent α=1.8±0.6. The ratio of ϕ to K− production yields seems not to depend, within the experimental uncertainties, on the collision centrality, and the average of measured values was found to be 0.36±0.05.